Shacklean Uncertainty and Cultural Embeddedness as Innovation Constraints in the UK - Annie Tubadji; Peter Nijkamp; Enrico Santarelli (Global Labor Organization (GLO), 2017)
We focus on both individual and local uncertainty to explain the innovation potential of entrepreneurs in the NUTS1 UK regions in 2005 and 2009. The `potential surprise function' (Shackle, 1949) clarifying why sometimes promising business choices are truncated is taken as a determinant of an entrepreneur's innovation decision. GEM (Global Entrepreneurship Monitor) data and data on psychological types are used in the empirical analysis. The econometric estimation strategy addresses both the issue of selection bias (due to uncertainty) and that of zero-inflated data (i.e., presence of only a few highly innovative actors in comparison to the majority in our sample). Findings suggest that local uncertainty is the predominant determinant of individual entrepreneurial choice. The regional effect appears to amount to about 4% of the innovation differences across NUTS1 UK regions, while almost one third of it is determined by the local level of uncertainty bias. Thus, the novelty of the present study is that it shows how differences in local cultural tolerance to uncertainty may explain differences in the quantity of truncated innovative ideas among localities.
Keywords: Z10; D81; R11; 330; potential surprise function; entrepreneurship; innovation; knowledge; epistemic uncertainty; cultural embeddedness; Culture Based Development; quality ladder